2005
DOI: 10.1111/j.1600-6143.2005.01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Glomerular Filtration Rate in Kidney Transplantation: Are the K/DOQI Guidelines Applicable?

Abstract: The kidney disease outcomes quality initiative (K/DOQI) guidelines introduced a classification of chronic kidney disease (CKD) based on the level of kidney function. In order to predict the glomerular filtration rate (GFR), they specifically recommended the use of the modification of diet in renal disease (MDRD) study and Cockcroft-Gault (C-G) equations.Since the performance of these estimates has been questioned, we sought to determine whether these recommendations might be applicable in renal transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 20 publications
0
29
0
2
Order By: Relevance
“…The applicability of the MDRD study equation in RTRs has been studied widely with conflicting results, although on balance it was shown to be the most accurate with the least bias when compared with other formulae used to estimate GFR (9)(10)(11)(12) as CKD stage 1T-2T according to the level of GFR alone, which is in contrast to the KDOQI guidelines for native CKD, where markers of kidney damage (i.e. proteinuria, scarring) are also required.…”
Section: Ckd Classificationmentioning
confidence: 99%
“…The applicability of the MDRD study equation in RTRs has been studied widely with conflicting results, although on balance it was shown to be the most accurate with the least bias when compared with other formulae used to estimate GFR (9)(10)(11)(12) as CKD stage 1T-2T according to the level of GFR alone, which is in contrast to the KDOQI guidelines for native CKD, where markers of kidney damage (i.e. proteinuria, scarring) are also required.…”
Section: Ckd Classificationmentioning
confidence: 99%
“…PubMed research (last accessed July 2010) recovered only 12 studies with mGFRs Ͼ100 reporting this performance of the CG and MDRD formulas, and their results are presented in Table 2 (6,44,72,90,92,95,99,(103)(104)(105)(106)(107). Comparing CG versus MDRD formula in studies with data for both formulas (6431 subjects) showed similar overall proper classification of the subjects, 64% versus 63%, range 55% to 72% versus 53% to 71%, respectively (6,72,92,95,99,(103)(104)(105)(106)(107). The best performance of CG and MDRD equations was in mGFR group 30 to 59 ml/min per 1.73 m 2 , whereas the worst one was in mGFR groups Ͻ15 and Ͼ90 ml/min per 1.73 m 2 , respectively.…”
Section: Effect Of Egfr On K/doqi-ckd Diagnosing and Stagingmentioning
confidence: 99%
“…In RTR the performance of urine-creatinine clearance and of many different prediction formulas has been found similar [14,25]. The comparison with isotopic measurement of GFR was often disappointing [26,27]. In particular, prediction errors of fformulas are much higher in patients with better renal function [28].…”
Section: Discussionmentioning
confidence: 99%